Global Assessment Report on Disaster Risk Reduction 2025 - United Nations Office for Disaster Risk Reduction (United Nations, 2025)
The Global Assessment Report (GAR) 2025: Resilience Pays: Financing and Investing for our Future highlights how smarter investment can reset the destructive cycle of disasters, debt, uninsurability and humanitarian need that threatens a climate-changed world. Disaster risk is increasing as more frequent and intense hazard events, unsafe urbanization and ineffective development put more people and assets in harm’s way. Disasters are having profound macroeconomic impacts, with direct losses estimated at 202 billion. When indirect and ecosystem costs are taken into account, escalating disaster costs now surpass 2.3 trillion annually. There is an urgent need to transform how disaster risk is addressed amid a rapidly changing climate. Risk is no longer a peripheral issue but a systemic challenge that affects financial stability, sustainability, and equity. By embedding risk reduction into core policy and investment decisions, it is possible to break the recurring cycle of shocks, losses and debt. With the right choices, resilience can become a foundation for long-term prosperity, enabling societies not only to withstand disasters but to thrive despite them.